Resident microbiota habitats and gut-balancing additives for poultry production: review (Research, Society and Development, 2021)
The resident microbiota of poultry presents a great variety of commensal and/or mutualistic microorganisms, which colonize from the crop, permeating through the proventriculus, ventricle, small intestine and its portions (duodenum, jejunum, ileum) and large intestine (cecum, colon, and rectum). They act in the metabolism of nutrients in the diet, generating important metabolites for the balance of the intestinal microbiota and in the preservation of the tissue wall of the intestinal organs, resulting in better use of the nutrients in the diet, as well as greater animal productivity. Knowledge about this ecosystem and how it works is extremely important, since through functional additives it is possible to influence the intestinal microbiota, improving the absorption and animal performance. This literature review has as its main objective to indicate the main aspects of the intestinal microbiota of poultry and their habitats, and some of the main microbiota-enhancing additives used in animal nutrition to ensure the health of the poultry intestinal environment. The methodology adopted was a descriptive study, resulting in a literature review based on worldwide scientific articles.